19.46%-Efficiency all-polymer organic solar cells with excellent outdoor operating stability enabled by active layer reconstruction - Wu, Xiaohei; Xiao, Bo; Sun, Rui; Yang, Xinrong; Zhang, Meimei; Gao, Yuan; Xiao, Biao; Papkovskaya, Elizaveta D.; Luponosov, Yuriy; Brabec, Christoph; Min, Jie (Energy and Environmental Science, 2025)
Morphology control has been critical engineering in establishing rapid charge transfer channels and enhancing the solidification of the bulk microstructure, ultimately leading to improved device performance. Herein, we synergistically combined layer-by-layer (LbL) doctor-blading deposition with a multicomponent controlling strategy to achieve favorable active layer reconstruction and thus fabricated quaternary all-polymer solar cells (all-PSCs). Compared to the quaternary bulk-heterojunction (Q-BHJ) system based on PM6:D18-Cl:PY-SSe:PY-Cl, the quaternary LbL (Q-LbL) system based on (D18-Cl:PY-Cl)/(PM6:PY-SSe) can significantly improve the optical and electronic properties, ensure charge transfer and extraction, and reduce non-geminate recombination loss. Consequently, the rigid and flexible Q-LbL all-PSCs exhibit outstanding power conversion efficiencies of 19.46% and 17.02%, respectively. In particular, the Q-LbL system showed promising thermal and mechanical stability as well as outdoor operational stability. These findings highlight the potential of the Q-LbL processing strategy to simultaneously improve the efficiency and stability of all-PSCs, thereby paving the way for their practical applications.
CRIS-Team Scopus Importer:2025-01-31